GENERASI MUDA DI PERSIMPANGAN JALAN (ANALISIS SEMIOTIK TERHADAP TOKOH LINTANG DALAM FILM LASKAR PELANGI REPRESENTASI KEGIGIHAN PELAJAR SD DI PELOSOK INDONESIA) - Ramadhani, Kartika Putri; Mondry, Mondry (Jurnal Interaktif, 2010)
Movie, as one of communication media, is very effective because of its power and ability to reach many social segments. Laskar Pelangi the Movie is Indonesian movie which uses educational as its theme. The movie, which is based on the true story, likely the real condition of amount of this country residents.The aim of this study is to comprehend the representation of Lintangâs determination to reach proper education in remote area in Laskar Pelangi the Movie. The method which is used in this study is qualitative descriptive semiotic analysis. The data analysis is done by semiotic analysis of Roland Barthes to discuss about the greater definition range in order to difference the denotative and connotative meaning from the signs of this movie.The first result of Roland Barthes semiotic analysis is end to the myth reading, and the myth that can be arrested in this movie is to reach education we also need enough material. Nevertheless, that myth can be broken by the other scene in this movie, that is the economic inability cannot stop someone to get what he or she dreamed especially education. Second, as a medium which can educates and critize, Laskar Pelangi the movie includes social critic to the goverment, parents, education practitioner, and also students.Key words: Movie, Semiotic Analysis, Lintang, Laskar Pelangi